Forest density intensifies the importance of snowpack to growth in water‐limited pine forests. Issue 1 (16th September 2020) - Gleason, Kelly E.; Bradford, John B.; D'Amato, Anthony W.; Fraver, Shawn; Palik, Brian J.; Battaglia, Michael A.
Abstract: Warming climate and resulting declines in seasonal snowpack have been associated with drought stress and tree mortality in seasonally snow‐covered watersheds worldwide. Meanwhile, increasing forest density has further exacerbated drought stress due to intensified tree–tree competition. Using a uniquely detailed data set of population‐level forest growth ( n  = 2, 495 sampled trees), we examined how inter‐annual variability in growth relates to snow volume across a range of forest densities (e.g., competitive environments) in sites spanning a broad aridity gradient across the United States. Forest growth was positively related to snowpack in water‐limited forests located at low latitude, and this relationship was intensified by forest density. However, forest growth was negatively related to snowpack in a higher latitude more energy‐limited forest, and this relationship did not interact with forest density. Future reductions in snowpack may have contrasting consequences, as growth may respond positively in energy‐limited forests and negatively in water‐limited forests; however, these declines may be mitigated by reducing stand density through forest thinning.